Penguatan Literasi Digital dalam Mengantisipasi Penyalahgunaan Teknologi Siswa di SDI Nurul Jadid Singosari - Sumiyati, Sumiyati; Rossidy, Imron (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
The purpose of writing this article is to find out how the process of strengthening digital literacy is in anticipating student misuse of technology and how strategies for strengthening digital literacy are carried out in anticipating student misuse of technology at SDI Nurul Jadid Singosari. The method used is a descriptive qualitative approach with data analysis used for collection, presentation and drawing conclusions. This type of research uses a case study type by focusing on one problem that you want to know and understand in depth and holistically. The results of the research reveal the process of strengthening digital literacy in anticipating misuse of student technology. It concludes that the process of strengthening digital literacy is carried out directly, which is included in the curriculum, such as directing students when they first enter as new students and enriching routine activities once every three months in collaboration with parents to anticipate The misuse of digital technology is then carried out indirectly, namely strengthening literacy carried out by teachers even though it is not included in the curriculum either inside or outside the classroom. The strategy to strengthen literacy is carried out by the school and teachers following activities listed in the curriculum related to direction, guidance and understanding the use of digital technology. However, in this strategy to strengthen digital literacy, the school gives authority to teachers regarding how the concept and method of strengthening literacy is carried out.